THE FUNCTION AND TYPES OF THE TRANSMISSION GEARBOX - Jomiyeva Shaxnoza Mamatqodir qizi (Ustozlar uchun, 2025)
Abstract:The transmission gearbox is a crucial component of an automobile’s powertrain system, responsible for transmitting power from the engine to the wheels while enabling the vehicle to operate at various speeds and torque levels. This article discusses the main functions of the transmission gearbox and classifies its common types, including manual, automatic, continuously variable (CVT), and dual-clutch transmissions (DCT). Understanding these types enhances knowledge of vehicle performance, fuel efficiency, and driving comfort.